New Pd(II) complexes of the bisthiocarbohydrazones derived from isatin and disubstituted salicylaldehydes: Synthesis, characterization, crystal structures and inhibitory properties against some metabolic enzymes - Kaya, Yeliz; Ercag, Ayse; Zorlu, Yunus; Demir, Yeliz; Gulcin, Ilhami (Springer, 2022)
Pd(II) complexes (Pd1, Pd2, and Pd3) were synthesized for the first time using asymmetric isatin bisthiocarbohydrazone ligands and PdCl2 (PPh3)(2). All complexes were characterized by a range of spectroscopic and analytical techniques. The molecular structures of Pd1 and Pd3 have been determined by single-crystal X-ray diffraction analysis. The complexes are diamagnetic and exhibit square planar geometry. The asymmetric isatin bisthiocarbohydrazone ligands coordinate to Pd(II) ion in a tridentate manner, through the phenolic oxygen, imine nitrogen and thiol sulfur, forming five- and six-membered chelate rings within their structures. The fourth coordination site in these complexes is occupied by PPh3 (triphenylphosphine). The free ligands and their Pd(II) complexes were evaluated for their carbonic anhydrase I, II (hCAs) and acetylcholinesterase (AChE) inhibitor activities. They showed a highly potent inhibition effect on AChE and hCAs. K-i values are in the range of 9 +/- 0.6 - 30 +/- 5.4 nM for AChE, 7 +/- 0.5 - 16 +/- 2.2 nM for hCA I and 3 +/- 0.3-24 +/- 1.9 nM for hCA II isoenzyme. The results clearly demonstrated that the ligands and their Pd(II) complexes effectively inhibited the used enzymes. [GRAPHICS] .
Keywords: Isatin; Bisthiocarbohydrazone; Palladium(II); Crystal structure; Carbonic anhydrase; Acetylcholinesterase